PERLINDUNGAN HUKUM TERHADAP PELAKU NOODWEER DALAM TINDAK PIDANA PEMBUNUHAN - Ekky Saputra; Maryano, Maryano; Hedwig Adianto Mau (Journal of Innovation Research and Knowledge, 2025)
As a manifestation of the principle of the rule of law, every criminal act, referred to in the Indonesian Penal Code (Kitab Undang-Undang Hukum Pidana or KUHP) as a criminal offense (delict), can only be resolved through the applicable legal mechanisms, namely criminal law. An individual may be acquitted of charges if proven not guilty or if the act of violence was committed in self-defense, as regulated under Article 49 of the KUHP, commonly known as "noodweer". The theories employed in this study include the theory of legal protection and the theory of justice. Additionally, the author provides a general review of evidence and noodweer based on various sources. This study adopts a normative juridical research approach. The author utilizes the statute approach and case approach, relying on legal materials derived from secondary data, which consist of primary legal materials, secondary legal materials, and tertiary legal materials. The data collected through library research is then analyzed descriptively. The findings of this study indicate that the legal provisions for individuals acting in noodweer in cases of homicide refer to Article 49(1) of the KUHP. This provision regulates "emergency defense" or "forced defense" (noodweer) carried out to protect oneself, others, morality, or property from an imminent and unlawful attack or threat of attack. The forms of legal protection granted to individuals acting in noodweer in cases of homicide align with the principle of justice in criminal law, which emphasizes a balance between individual rights protection and legal interests. These forms of legal protection include: Exemption from punishment (strafuitsluitingsgrond), The right to present a defense in court, The right to legal assistance, and Judicial considerations in rendering a verdict, where judges have the discretion to assess whether an act qualifies as noodweer or falls under the category of noodweer excess (excessive self-defense).